Efficiency of compost and vermicompost in supporting the growth and chemical constituents of salvia officinalis L. Cultivated in Sand Soil - M. E. El-Haddad; Mona S Zayed; G.A.M. El-Sayed; Amal M. Abd EL-Satar (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The effect of using compost and vermicompost or their teas on the growth and biochemical profile of Salvia officinalis cultivated in sand soil were assessed. Methods Plants were subjected to different treatments of compost, vermicompost and their teas. The growth of common sage, Salvia officinalis was monitored as shoot fresh and dry weights (g/plant) and their oil, N, P, and K contents. Results Among the four tested treatments of vermicompost, the treatment no. 1 (prepared from rice straw supplemented by Trichoderma harzianum and Phanerochaete chrysosporium + Cattle dung + Rock phosphate + Feldspar “12 % K2O”), showed the maximal values of shoot fresh and dry weights, oil, N, P, and K %, being in the first cut 820, 200 g/plant, 1.42, 2.80, 1.40 and 1.98 in respective order. The corresponding values in the second cut were 1152, 277 g/plant, 1.55, 3.56, 1.68 and 2.29%, respectively. Also, the maximal values of all previous parameters were recorded in the vermicompost tea treatment no1, treated as soil and foliar amendments being 730, 196 g/plant, 1.47, 2.4, 1.38 and 2.19% in the first cut and 1150, 270 g/plant, 1.64, 3.5, 1.68 and 2.38% in the second cut, respectively. Conclusions The growth of Salvia officinalis was higher in plants treated by different vermicompost treatments, compared to those treated by compost or the control (without any supplementation).